REPRODUCTIVE POTENTIAL IN MACROBRACHIUM MALCOLMSONII (EDWARDS) FROM RIVER OJAT, NAVIBANDAR, SAURASHTRA (INDIA) - Mansuri, A P; Patel, R I; Kundu, Rahul; Krishnan, Smita; Parvez, Rishad (Indian Journal of Fisheries, 2011)
The reproductive potential in the form of fecundity was estimated in M. malcolmsonii from river Ojatof Saurashtra (1983 & '84).The results indicated fecundity ranging from 5,100 to 83,000 in the berried females of 63.0 mm to204.0 ram length size. The relationship of body length, with fecundity was significant but it was highlysignificant (r = 0.99) between egg-mass weight and fecundity